Effectiveness of Wii-based rehabilitation in stroke: A randomized controlled study - Ayça Utkan Karasu; Elif Balevi Batur; Gülçin Kaymak Karataş (Medical Journals Sweden, 2018)
Objective: To investigate the efficacy of Nintendo Wii Fit®-based balance rehabilitation as an adjunc-tive therapy to conventional rehabilitation in stroke patients. Methods: During the study period, 70 stroke patients were evaluated. Of these, 23 who met the study criteria were randomly assigned to either the experimental group (n = 12) or the control group (n = 11) by block randomization. Primary outcome measures were Berg Balance Scale, Functional Reach Test, Postural Assessment Scale for Stroke Patients, Timed Up and Go Test and Static Balance Index. Secondary outcome measures were postural sway, as assessed with Emed-X, Functional Independence Measure Transfer and Ambulation Scores. An evaluator who was blinded to the groups made assessments immediately before (baseline), immediately after (post-treatment), and 4 weeks after completion of the study (follow-up). Results: Group-time interaction was significant in the Berg Balance Scale, Functional Reach Test, anteroposterior and mediolateral centre of pressure displacement with eyes open, anteroposterior centre of pressure displacement with eyes closed, centre of pressure displacement during weight shifting to affected side, to unaffected side and total centre of pressure displacement during weight shifting. Demonstrating significant group-time interaction in those parameters suggests that, while both groups exhibited significant improvement, the experimental group showed greater improvement than the control group. Conclusion: Virtual reality exercises with the Nintendo Wii system could represent a useful adjunctive therapy to traditional treatment to improve static and dynamic balance in stroke patients.